The wide window - Snicket, Lemony; Helquist, Brett (New York : HarperTrophy, 2000)
Catastrophes and misfortune continue to plague the Baudelaire orphans after being sent to live with fearful Aunt Josephine, who offers little protection against Count Olaf's treachery.
AAL
Keywords: Orphans -- Fiction; Brothers and sisters -- Fiction; City and town life -- Fiction; Humorous stories